Fundus Changes In Pregnancy Induced Hypertension - Karki, Poojyashree; Basnet, PS; Basnet, A; Sijapati, MJ; KC, Manish; Pokharel, K (Journal of Universal College of Medical Sciences, 2018)
BACKGROUND: Ocular involvement in Pregnancy Induced Hypertension (PIH) is common. Hypertensive disorders have a propensity to involve the vascular tissue, which makes the ocular vessels particularly susceptible. Widespread changes in the conjunctiva, retina, vessels, choroid, optic nerve, and occipital cortex have been documented in these patients; some of them leading to decreased vision too.Various studies have correlated the fundus changes with maternal and foetal outcomes and documented the progression of retinal vascular changes a sign of increasing severity of PIH. So this study was carried out to find out fundus changes in PIH. MATERIALS & METHODS: Study design was retrospective descriptive type. Records of 96 patients admitted in the Obstetrics ward, KIST Medical College Teaching Hospital, Imadol, Lalitpur, Nepal, with the diagnosis of PIH were reviewed and duration of study was 3 years (October 2010 – October 2013). Patients were evaluated for hypertensive fundus changes. RESULTS: Fundus changes were found in 16.6% patients of PIH. Fundus findings comprised of vascular changes, extravascular retinal changes, optic neuropathy and choroidopathy. Vitreous hemorrhage, serous retinal detachment and macular star were not found in this study. CONCLUSION: Fundus evaluation in patients with PIH is an important part of their management as there are various fundus changes found in these patients which may lead to decrease in vision. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, page: 42-44